2019
DOI: 10.1111/jdv.15413
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental autoimmune disease and atopic dermatitis in their offspring: a matched case–control study

Abstract: Background Atopic dermatitis (AD) is associated with many autoimmune diseases, in part due to overlapping genetic risk loci. While parental atopic disease is an important risk for AD in the offspring, little is known on the putative associations between parental autoimmune disease and AD in their children. Materials and methods All children born between 1996 and 2011 who received a diagnosis of AD in the hospital system before their fifth birthday were matched 1 : 10 with children from the general population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
(165 reference statements)
0
12
0
Order By: Relevance
“…Maternal systemic lupus erythematosus has been associated with child asthma, anaphylaxis, and other allergic conditions in a few reports 2,3 . Studies have found that the relationship between parental autoimmune disease and child allergy is either maternal‐specific, 22 or related to both maternal and paternal disease 19 …”
Section: Discussionmentioning
confidence: 99%
“…Maternal systemic lupus erythematosus has been associated with child asthma, anaphylaxis, and other allergic conditions in a few reports 2,3 . Studies have found that the relationship between parental autoimmune disease and child allergy is either maternal‐specific, 22 or related to both maternal and paternal disease 19 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, HLA polymorphisms have also been reported to be associated with AA severity. 11,22,23 The current study showed a higher risk of autoimmune outcomes in offspring born to mothers with AT/AU than in offspring born to mothers with PA.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have shown a strong association between HLA antigens and AA. 11,[17][18][19][20] It has been shown that HLA polymorphisms may act as susceptibility factors. In addition, coding for the HLA DRB1 allele and related gene variants affects cytokines and toll-like receptors, which in turn influences the patho-genesis of atopic disorders due to the innate/adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atopy has been associated with classical autoimmune disorders and AD may co-occur with autoimmune diseases (psoriasis, rheumatoid arthritis, multiple sclerosis and type I diabetes mellitus). In a matched case–control study, including 8589 children with diagnosed AD before the age of 5 and 85,890 controls, the association between parental autoimmune disease and the development of AD in their offspring were studied [ 25 ]. The presence of maternal (not paternal), dermatologic or digestive autoimmune disease was associated with an increased risk for development of AD in their offspring.…”
Section: The Association Of Atopic Dermatitis and Autoimmunitymentioning
confidence: 99%